ASEAN international mobility for students (aims) going global: students’ perception - Saikim, Fiffy Hanisdah; Mohd Nordin, Nordiana; Khalid, Jamshed; Abdul Aziz, Nor Akmar (GADING Journal for the Social Sciences, 2023)
ASEAN International Mobility for Students (AIMS) upsurges several opportunities for ASEAN students and higher education administrators operating in the ASEAN region. This study aims to investigate the effectiveness of the AIMS program from the students’ perception of studying in Malaysian higher education institutions (HEIs). The study explores the program’s impact on participants by highlighting personal and professional development. Twenty-four students from ten Malaysian universities participated in this study through in-depth interviews. The data were analyzed by semantic extraction and relational extraction in Leximancer. Connectivity rates in Leximancer analysis reveal that respondents understand the importance of AIMS Global for academic progression, international skills development, and holistic education through quality teaching and learning. Respondents urge the need for the AIMS program to expand its local wings into global so that students learn from cultural diversity. Finally, respondents advocate that AIMS programs would be helpful for graduates’ employability by enhancing their creativity and English language skills. These findings may assist the AIMS administrators and ASEAN educational leadership in observing the beneficial impact of regional and global mobility.